Strategi Politik PDIP Dalam Pemenangan Pasangan Ganjar â€“ Heru di Pilgub Jawa Tengah Tahun 2013 - Dian Purnama, Angga Arrasyid; Utomo, Susilo; Martini, Rina (Journal of Politic and Government Studies, 2014)
The purpose of this study is to analyze the political strategy used by Partai Demokrasi Indonesia Perjuangan in the Central Java Governor Election 2013. In that election, PDIP carried its main cadres, Ganjar Pranowo and Heru Sudjatmoko, without a coalition with another party because they believed they could win the Central Java governor election (Pilgub Jateng) by themselves, and most importantly, they thought that if they win that election, they will be able to run the Central Java governance with their own ideology, without considering another ideology from the coalition party. And then, what about PDIP political strategy in the Central Java Governor and Deputy Governor Election 2013, in order to be able to win the vote? Although Central Java is the PDIP mass base, but2we need to realize that both opponent candidates of Ganjar-Heru were the incumbent government in Central Java.In this study, the researcher uses â€œthe descriptive-narrativeâ€ qualitative research methods. Hopefully, this study will be able to describe the strategy that was used by PDIP in chronological way, so it will be easy to read and able to give a deeper assessment and discussion. The data were obtained through observations, interviews with all their supporting team and PDIP cadres who were involved in the process of succeeding Ganjar-Heru in the Central Java Governor Election, as well as the data obtained from the documents.Political strategies that were used by Partai Demokrasi Indonesia Perjuangan in the Central Java Governor Election 2013, conducted in the form of political campaign strategy, image/figure strategy, the mass-base strategy, pairing the prominent candidate with fellow popular PDIP cadre, community approach strategy, and general strategy. The strategies combination eventually could make Ganjar-Heru win the election with 6,962,417 votes or 48.82 % of the vote. Ganjar-Heru beat HP-Don and Bibit- Sudijono each with 20.92 % and 30.26 % of the vote.